2022
DOI: 10.1002/sd.2399
|View full text |Cite
|
Sign up to set email alerts
|

Do green innovation and financial globalization contribute to the ecological sustainability and energy transition in the United Kingdom? Policy insights from a bootstrap rolling window approach

Abstract: Environmental sustainability and energy transition, especially the renewable energy transition, have become critical concerns of nations throughout the world in recent decades.The sustainable and eco-friendly technologies have led to more sustainable methodologies, substantial stewardship of our natural resources, and the conversion to renewable energy sources, all of which have been demonstrated to benefit the environment significantly. However, prior studies have overlooked the ecological sustainability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(51 citation statements)
references
References 128 publications
(174 reference statements)
1
30
0
Order By: Relevance
“…There is global concern regarding the rapid increase in greenhouse gas emissions, which presents particular difficulties for life on Earth. Evidently, the manner in which humans have used energy in recent decades has contributed strongly to an increase in ecological degradation (Chen et al, 2019; Ramzan et al, 2022). Furthermore, the impact of the existing level of greenhouse gases (GHGs) will persist even if such emissions are reduced.…”
Section: Introductionmentioning
confidence: 99%
“…There is global concern regarding the rapid increase in greenhouse gas emissions, which presents particular difficulties for life on Earth. Evidently, the manner in which humans have used energy in recent decades has contributed strongly to an increase in ecological degradation (Chen et al, 2019; Ramzan et al, 2022). Furthermore, the impact of the existing level of greenhouse gases (GHGs) will persist even if such emissions are reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Irfan et al (2022) studied the dynamic relationship between financial development, economic growth and carbon emissions in the UK, and pointed out that pollution from fossil fuels will hinder the improvement of long-term productivity and policymakers should increase support for financial markets and green energy. Ramzan et al (2022) investigate the role of green innovation and financial globalization on the sustainability of the environment and energy transition using a time-varying rolling window model based on quarterly data from 1995 to 2020 in the United Kingdom and found that innovation in green technologies and energy transition are both beneficial for environmental sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, demonstrated using the MMQR technique that financial globalisation dissuades ecological sustainability in BRICS countries. In a related study for the United Kingdom, Ramzan et al (2022) found, with the aid of a time-varying rolling window method, that financial globalisation aids environmental sustainability.…”
Section: Globalisation and Sd Nexusmentioning
confidence: 99%